The longitudinal biomonitoring of residents living near the waste incinerator of Turin: Polycyclic Aromatic Hydrocarbon metabolites after three years from the plant start-up. (1st December 2022) - Iamiceli, A.L.; Abate, V.; Bena, A.; De Filippis, S.P.; De Luca, S.; Iacovella, N.; Farina, E.; Gandini, M.; Orengia, M.; De Felip, E.; Abballe, A.; Dellatte, E.; et al.
Abstract: The waste-to-energy (WTE) incinerator plant located in the Turin area (Italy) started to recover energy from the combustion of municipal solid waste in 2013. A health surveillance program was implemented to evaluate the potential health effects on the population living near the plant. This program included a longitudinal biomonitoring to evaluate temporal changes of some environmental pollutants, including polycyclic aromatic hydrocarbons (PAHs), in residents living in areas near the Turin incinerator (exposed group, E) compared to those observed in subjects living far from the plant (not exposed group, NE). Ten monohydroxy-PAHs (OH-PAHs), consisting in the principal metabolites of naphthalene, fluorine, phenanthrene, and pyrene, were analyzed in urines collected from the E and NE subjects after one (T1 ) and three years (T2 ) of plant activity and compared with those determined in the same cohort established before the plant start-up (T0 ). Spearman correlation analysis was undertaken to explore possible associations between OH-PAHs and personal characteristics, lifestyle variables, and dietary habits. A linear mixed model (LMM) approach was applied to determine temporal trends of OH-PAHs observed in the E and NE subjects and to evaluate possible differences in trend between the two groups. Temporal trends of OH-PAHs determined by LMM analysis demonstrated that, at all times, the E group had concentrations lower than those assessed in the NE group, all other conditions being equal. Moreover, no increase in OH-PAH concentrations was observed at T1 and T2 either in E or in NE group. Significant positive correlations were found between all OH-PAHs and smoking habits. Regarding variables associated to outdoor PAH exposure, residence near high traffic roads and daily time in traffic road was positively correlated with 1-hydroxynaphthalene and 1-hydroxypyrene, respectively. In conclusion, no impact of the WTE plant on exposure to PAHs was observed on the population living near the plant. Graphical abstract: Image 1 Highlights: Human exposure to waste incinerator emissions is of great concern. No impact of the WTE plant was observed on human exposure to PAHs. OH-PAH levels did not increase after one and three years of incinerator activity. Temporal trends of OH-PAH levels did not differ among exposed and not-exposed group.